Pseudorabies Virus Glycoprotein gK Is a Virion Structural Component Involved in Virus Release but Is Not Required for Entry - Klupp, Barbara G. (American Society for Microbiology, 1998)
The pseudorabies virus (PrV) gene homologous to herpes simplex virus type 1 (HSV-1) UL53, which encodes HSV-1 glycoprotein K (gK), has recently been sequenced (J. Baumeister, B. G. Klupp, and T. C. Mettenleiter, J. Virol. 69:5560–5567, 1995). To identify the corresponding protein, a rabbit antiserum was raised against a 40-kDa glutathione S-transferase–gK fusion protein expressed in Escherichia coli. In Western blot analysis, this serum detected a 32-kDa polypeptide in PrV-infected cell lysates as well as a 36-kDa protein in purified virion preparations, demonstrating that PrV gK is a structural component of virions. After treatment of purified virions with endoglycosidase H, a 34-kDa protein was detected, while after incubation with N-glycosidase F, a 32-kDa protein was specifically recognized. This finding indicates that virion gK is modified by N-linked glycans of complex as well as high-mannose type. For functional analysis, the UL53 open reading frame was interrupted after codon 164 by insertion of a gG-lacZ expression cassette into the wild-type PrV genome (PrV-gKβ) or by insertion of the bovine herpesvirus 1 gB gene into a PrV gB(−) genome (PrV-gK(gB)). Infectious mutant virus progeny was obtained only on complementing gK-expressing cells, suggesting that gK has an important function in the replication cycle. After infection of Vero cells with either gK mutant, only single infected cells or small foci of infected cells were visible. In addition, virus yield was reduced approximately 30-fold, and penetration kinetics showed a delay in entry which could be compensated for by phenotypic gK complementation. Interestingly, the plating efficiency of PrV-gKβ was similar to that of wild-type PrV on complementing and noncomplementing cells, pointing to an essential function of gK in virus egress but not entry. Ultrastructurally, virus assembly and morphogenesis of PrV gK mutants in noncomplementing cells were similar to wild-type virus. However, late in infection, numerous nucleocapsids were found directly underneath the plasma membrane in stages typical for the entry process, a phenomenon not observed after wild-type virus infection and also not visible after infection of gK-complementing cells. Thus, we postulate that presence of gK is important to inhibit immediate reinfection.